2017
DOI: 10.1111/jan.13497
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting Registered Nurses’ intentions to leave their organization and profession: A job demands‐resources framework

Abstract: Employee burnout and work engagement play an important role in transmitting the impacts of job demands, job resources, personal demands and personal resources into RN intention to leave the organization and profession. Work-life interference and high workloads are major threats to nursing retention while challenge demands and higher levels of self-efficacy support better retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
220
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(235 citation statements)
references
References 66 publications
(109 reference statements)
13
220
0
2
Order By: Relevance
“…Furthermore, burnout could affect nurses' career advancement. Previous studies suggested that burnout was associated with decreased nurses' job satisfaction and higher odds of intension to leave (Liu, While, Li, & Ye, ; Moloney et al, ). These negative aspects of job burnout might have implications for nurses' QoWL.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, burnout could affect nurses' career advancement. Previous studies suggested that burnout was associated with decreased nurses' job satisfaction and higher odds of intension to leave (Liu, While, Li, & Ye, ; Moloney et al, ). These negative aspects of job burnout might have implications for nurses' QoWL.…”
Section: Discussionmentioning
confidence: 94%
“…High‐level WE is conducive to take full advantage of available job resources and is associated with positive outcomes. In line with the theory, engaged workers, who are deeply engrossed in their work, usually present a low tendency to leave the organization (Moloney et al, ). Therefore, we assumed that WE had a direct association with TI (hypothesis 1).
Hypothesis 1: Work engagement has a direct negative association with turnover intention among community nurses
…”
Section: Theory Framework and Hypothesesmentioning
confidence: 89%
“…This motivational process connects job resources with work outcomes via WE. In this study, OJ and OS, as two kinds of important job resources, could promote WE through intrinsic and extrinsic motivation and then contribute to positive outcomes such as lower intention to turn over (Moloney et al, ). Therefore, in view of the motivational process and indirect associations, we proposed hypotheses 6 and 7.
Hypothesis 6: Organisational justice has an indirect negative association with turnover intention mediated by work engagement among community nursesHypothesis 7: Organisational support has an indirect negative association with turnover intention mediated by work engagement among community nurses
…”
Section: Theory Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Competing demands between personal and work roles can result in personal conflicts (Ghislieri, Gatti, Molino, & Cortese, ; Moloney et al, ). This study gave support to an inverse relationship between workload and nurse aspiration to enter management.…”
Section: Discussionmentioning
confidence: 99%